Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T19:26:28+01:00
3(x-0,5)+2(y+3)=3,5
(3x-1)/3-(y+3)/2=-1 /*6

3x -1,5 +2y +6 = 3,5
2(3x-1) -3(y +3) = - 6

3x + 2y = 3,5 - 4,5
6x -2 -3y -9 = -6

3x +2y = -1
6x - 3y = -6 + 11

3x= -1 -2y
6x - 3y = 5

x = 1/3(-1-2y)
6*1/3(-1-2y) -3y = 5

x = 1/3(-1-2y)
2(-1-2y) -3y = 5

x = 1/3(-1-2y)
-2 -4y -3y = 5

x =1/3(-1-2y)
-7y = 5 +2

x = 1/3(-1-2y)
y = 7 : (-7)

x = 1/3(-1-2y)
y = - 1

x = 1/3[ -1 -2*(-1)]
y = - 1

x = 1/3[ -1 + 2]
y = - 1

x = 1/3*1
y = - 1

x = 1/3
y = - 1
2010-02-02T19:39:14+01:00
3(x-0,5)+2(y+3)=3,5
(3x-1)/3-(y+3)/2=-1 /*6

3x-1,5+2y+6=3,5
6x-2-3y-9=-6

3x+2y=-1 /(-2)
6x-3y=5

-6x-4y=2
6x-3y=5
_________
-7y=7

y=-1
x=1/3